Smart City: Concept, Models, Technologies, Standardization - Yershova, O. L.; Bazhan, L. I. (Statistics of Ukraine, 2020)
The digital transformation problems of modern urban economy are considered. Their relevance for Ukrainian cities is caused by the fact that there are already a significant number of "smart cities" in the world, which are comfortable for their residents and for the management of urban services. The outlined problem for Ukraine is that a complex scenario of intellectualization and digital transformation of Ukrainian cities has not been formed yet. Unresolved problems and challenges that hinder the digital transformation of Ukrainian cities, namely the lack of municipal information networks, are described. Areas of further research are outlined, in particular, the statistical study of "smart cities", which is based on the collection and application of large data for this purpose, as well as the implementation of foreign experience in the Ukrainian realities of the economy. The digital transformation of cities is reviewed as a change of existing business models of urban services, the creation of smart mobility, smart resource consumption. An infographic unity of resources, services and management systems should be created in order to coordinate the actions of related structures and services in case of emergencies and unforeseen situations. This involves increasing technological literacy for different segments of the urban population. Three models of "smart cities" are proposed, the successful operation of each depends on investment, their rational management, as well as improving the level of digital skills of the population. The manufacturability of urban infrastructure should be based on megatrends in the field of information technology, namely: mobility, social communications, cloud technologies, big data and predictive analytics, machine learning and artificial intelligence, cybersecurity technology, the Internet of Things. These technologies are end-to-end for the whole set of technological solutions developed for "smart" cities. The scenario of development of "smart city" from the technological point of view is described; its basic components are: smart physical infrastructure; smart digital infrastructure; digital platforms; integrated digital platforms. The idea of building a digital duplicate, which is an accurate reflection of the real city in digital reality - the information comes to it from various sensors, monitoring systems and resource counters. The received experience of functioning can be translated into reality if it is successful, or to refuse it. All this is done at minimal cost, time savings and without harm to the real city. It is concluded that: information and communication technologies in the field of housing and communal services ensure the reliability and security of urban systems and resource efficiency; the formation of "smart cities" in Ukraine is limited by the lack of technical base for the creation of information technology platforms; a roadmap for the digital transformation of the national economy has not been developed.